KELAYAKAN USAHA PENGOLAHAN IKAN ASIN DI KELURAHAN SUMBER JAYA KECAMATAN KAMPUNG MELAYU KOTA BENGKULU - Reswita Reswita (Jurnal Agrisep)
The aims of this research is to analyze the feasibility of salted fish processing in Kampung Melayu Bengkulu City. The respondents in the research are 20 salted fish processors. Those respondents are conducted by purposive with the method of collecting is census method. The methods used in analyzing the data are income analysis, R/C ratio, and ROI (Return of Investment). The result shows that the income from salted fish processing is about Rp.134.457,15; while the R/C ratio is 1,2; and ROI 9,76%. From the research can be concluded that the salted fish business is feasible.